2000
DOI: 10.1098/rspb.2000.1096
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the dissolved inorganic carbon concentration and growth rate in marine phytoplankton

Abstract: A range of marine phytoplankton was grown in closed systems in order to investigate the kinetics of dissolved inorganic carbon (DIC) use and the in£uence of the nitrogen source under conditions of constant pH. The kinetics of DIC use could be described by a rectangular hyperbolic curve, yielding estimations of K G(DIC) (the half saturation constant for carbon-speci¢c growth, i.e. C·) and · max (the theoretical maximum C·). All species attained a K G(DIC) within the range of 30^750 mM DIC. For most species, NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 56 publications
7
71
0
2
Order By: Relevance
“…Cyanobacterial growth increased significantly after enrichment with CO 2 or Pi (Fig. 1), which confirms previous studies with other algae (Burkhardt & Riebesell 1997, Burkhardt et al 1999, Clark & Flynn 2000Kim et al 2006;Posselt et al 2009;Kranz et al 2010). Explanations for the rising growth in C. raciborskii might be the lowering of the requirement of light energy for the CCM or HCO 3 2 transportation at enriched CO 2 levels or providing an advantage over more constant inputs for its cellular energy transduction at elevated Pi concentrations.…”
Section: Discussionsupporting
confidence: 78%
“…Cyanobacterial growth increased significantly after enrichment with CO 2 or Pi (Fig. 1), which confirms previous studies with other algae (Burkhardt & Riebesell 1997, Burkhardt et al 1999, Clark & Flynn 2000Kim et al 2006;Posselt et al 2009;Kranz et al 2010). Explanations for the rising growth in C. raciborskii might be the lowering of the requirement of light energy for the CCM or HCO 3 2 transportation at enriched CO 2 levels or providing an advantage over more constant inputs for its cellular energy transduction at elevated Pi concentrations.…”
Section: Discussionsupporting
confidence: 78%
“…While cell division of Emiliania huxleyi was not found to be affected by elevated CO 2 concentrations in previous studies (Buitenhuis et al, 1999;Clark and Flynn, 2000;Rost et al, 2002) a slight decrease in cell division rate with rising CO 2 was observed in this investigation. This difference may be due to the broader range of CO 2 levels applied here.…”
Section: Cell Division Rate and Diametermentioning
confidence: 64%
“…The impact of increased pCO 2 on primary production has been investigated theoretically as well as experimentally. Some authors report small, if any, effects (Clark and Flynn, 2000;Tortell et al, 2002), whereas others document a clear increase in primary production with increasing pCO 2 (Hein and Sand-Jensen, 1997;Schippers et al, 2004;Riebesell et al, 2007). The effect of seawater carbonate chemistry on photosynthesis rates thereby strongly depends on the presence and characteristics of cellular CO 2 -concentrating mechanisms (CCMs; Rost et al, 2003, Giordano et al, 2005.…”
Section: A Engel Et Al: Co 2 Increases 14 C Primary Productionmentioning
confidence: 99%